A comparative study on visual and optical performance of Akreos AO and Kontur AB IOLs after phacoemulsification cataract surgery - Gharaee, Hamid (J Curr Ophthalmol, 2016)
PURPOSE: Akreos AO and Kontur AB are two commonly used intraocular lenses (IOLs) in Iran. This study was designed to evaluate the visual performance of these lenses. METHODS: In a comparative interventional study, 35 patients (70 eyes) were recruited, and each IOL was implanted in one eye of the patients, randomly. Best corrected visual acuity (BCVA), contrast sensitivity, aberrometric analysis, and depth of focus were evaluated 1 month and 3 months postoperatively. A visual quality questionnaire was also filled for each eye, and the results were compared. RESULTS: Mean age of the patients was 60.97 ± 7.00 years. BCVA was not significantly different between the two eyes, before, 1 month, and 3 months postoperatively (p > 0.05 for all). Photopic and mesopic contrast sensitivity was not different between the two lenses instead of photopic 18 cycles per degree, 3 months postoperatively and in mesopic 6 cycles per degree 1 month postoperatively (p = 0.034 and p = 0.002, respectively). Aberrometric factors including HoRMS, Total RMS, and Higher order without Z(4,0) were not significantly different between the two lenses (p > 0.05 for all), but they were slightly lower for Akreos AO. Post-operative distance-corrected visual acuity for intermediate and near vision were not different between the two groups (p > 0.05, respectively). CONCLUSION: Visual performance of Akreos AO and Kontur AB is similar. However, contrast sensitivity and aberrometric parameters are slightly better for Akreos AO IOL.